LFP and oscillations—what do they tell us?. (April 2015) - Friston, Karl J; Bastos, André M; Pinotsis, Dimitris; Litvak, Vladimir
Highlights: A brief treatment of dynamic coordination in terms of predictive coding. Understanding synchronous message passing in terms of hierarchical predictive coding. Characterising cortical gain control with the dynamic causal modelling of neural fields. Characterising pathophysiological oscillations with dynamic causal modelling of neural masses. Abstract : This review surveys recent trends in the use of local field potentials—and their non-invasive counterparts—to address the principles of functional brain architectures. In particular, we treat oscillations as the (observable) signature of context-sensitive changes in synaptic efficacy that underlie coordinated dynamics and message-passing in the brain. This rich source of information is now being exploited by various procedures—like dynamic causal modelling—to test hypotheses about neuronal circuits in health and disease. Furthermore, the roles played by neuromodulatory mechanisms can be addressed directly through their effects on oscillatory phenomena. These neuromodulatory or gain control processes are central to many theories of normal brain function (e.g. attention) and the pathophysiology of several neuropsychiatric conditions (e.g. Parkinson's disease).